Imaging the East European Craton margin in northern Poland using extended correlation processing of regional seismic reflection profiles - Mężyk, Miłosz; Malinowski, Michał; Mazur, Stanisław (Solid Earth, 2019)
In NE Poland, Eastern European Craton (EEC) crust of Fennoscandian affinity is concealed under a Phanerozoic platform cover and penetrated by sparse, deep research wells. Most of the inferences regarding its structure rely on geophysical data. Until recently, this area was covered only by the wide-angle reflection and refraction (WARR) profiles, which show a relatively simple crustal structure with a typical three-layer cratonic crust. ION Geophysical PolandSPAN ™ regional seismic programme data, acquired over the marginal part of the EEC in Poland, offered a unique opportunity to derive a detailed image of the deeper crust. Here, we apply extended correlation processing to a subset ( ∼950 km) of the PolandSPAN ™ dataset located in NE Poland, which enabled us to extend the nominal record length of the acquired data from 12 to 22 s ( ∼60 km of depth). Our new processing revealed reflectivity patterns, which we primarily associate with the Paleoproterozoic crust formed during the Svekofennian (Svekobaltic) orogeny, that are similar to those observed along the BABEL and FIRE profiles in the Baltic Sea and Finland, respectively. We propose a mid- to lower-crustal, orogeny-normal lateral flow model to explain the occurrence of two sets of structures that can be collectively interpreted as kilometre-scale S–C ′ shear zones. The structures define a penetrative deformation fabric invoking ductile extension of hot orogenic crust in a convergent setting. Localized reactivation of these structures provided conduits for subsequent emplacement of gabbroic magma that produced a Mesoproterozoic anorthosite–mangerite–charnockite–granite (AMCG) suite in NE Poland. Delamination of thickened orogenic lithosphere may have accounted for magmatic underplating and fractionation into the AMCG plutons. We also found sub-Moho dipping mantle reflectivity, which we tentatively explain as a signature of the crustal accretion during the Svekofennian orogeny. Later tectonic phases (e.g. Ediacaran rifting, Caledonian orogeny) did not leave a clear signature in the deeper crust; however, some of the subhorizontal reflectors below the basement, observed in the vicinity of the AMCG Mazury complex, can be alternatively linked with lower Carboniferous magmatism.